IMPLEMENTATION OF SMART ASN-BASED STATE CIVIL APPARATUS COMPETENCY DEVELOPMENT PROGRAM IN THE GOVERNMENT OF SIBOLGA SAMBAS DISTRICT, SIBOLGA CITY - Fauziah Nur Simamora,; Andes Fuady Dharma Harahap,; Darman Syah Pulungan,; Muhammad Sein,; Nur Ainun Siregar,; Melisa Putri, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The enactment of Indonesian law No. 5 of 2014 concerning the State Civil Apparatus (ASN) is the main driving factor in determining the success of a governance that focuses on employee performance that creates effective work productivity. This study aims to analyze the effect of the Smart ASN program on improving employee competence in the Sibolga Sambas District Government. The main focus of this research includes three variables, namely human resource management (HRM), Smart ASN employees, and socialization of the Smart ASN program. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis techniques through the SmartPLS application. The test results show that HR management has a significant influence on the formation of Smart ASN employees. Smart ASN employees have a positive impact on increasing employee competence and the success of the socialization of the Smart ASN program. In addition, Smart ASN employees act as mediators that strengthen the relationship between HR management with increased competence and the effectiveness of the socialization of the implementation of the Smart ASN program. This finding shows that effective HR management strategies can form ASNs that are adaptive to change and technology. The active role of employees in supporting the implementation of the Smart ASN program is an important factor in creating an innovative work environment. Therefore, competency development through the Smart ASN approach can be the basis for sustainable bureaucratic reform and improving the quality of public services.